Counseling Women Who Have Experienced Pregnancy Loss: A Review of the Literature. Issue 1 (April 2015) - Randolph, Amber L.; Hruby, Brittaney T.; Sharif, Shaakira
<x xml:space="preserve">Abstract</x> The authors review pregnancy loss scholarly literature and discuss themes of silence, grief, psychological distress, role of social support, satisfaction with health care, and coping strategies from a counseling standpoint. Counseling needs of women who have experienced pregnancy loss are delineated, and recommendations for future research in this area are made.